Development of Genetic Markers for Triploid Verification of the Pacific Oyster, - Jung-Ha Kang (Asian-Australasian Journal of Animal Sciences, 2013)
The triploid Pacific oyster, which is produced by mating tetraploid and diploid oysters, is favored by the aquaculture industry because of its better flavor and firmer texture, particularly during the summer. However, tetraploid oyster production is not feasible in all oysters; the development of tetraploid oysters is ongoing in some oyster species. Thus, a method for ploidy verification is necessary for this endeavor, in addition to ploidy verification in aquaculture farms and in the natural environment. In this study, a method for ploidy verification of triploid and diploid oysters was developed using multiplex polymerase chain reaction (PCR) panels containing primers for molecular microsatellite markers. Two microsatellite multiplex PCR panels consisting of three markers each were developed using previously developed microsatellite markers that were optimized for performance. Both panels were able to verify the ploidy levels of 30 triploid oysters with 100% accuracy, illustrating the utility of microsatellite markers as a tool for verifying the ploidy of individual oysters.